Detection of BCR-ABL T315i mutation in imatinib resistant chronic myeloid leukemia patients - Mardziah M; Salwati Shuib; Azlin Ithnin; Hafiza Alauddin; Noor Farisah AR; Noraesah M; Tumian NR; Wong, CL; Raja Zahratul Azma Raja Sabudin (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Chronic myeloid leukemia (CML) patients who have BCR-ABL T315I mutation, usually present in the advance phase of the disease with overall survival (OS) shorter than those without the mutation. This study aimed to determine the prevalence of T315I mutation amongst imatinib mesylate (IM) resistant CML patients and to compare the OS between T315I-mutated and non-T315I-mutated patients. Sixty consecutive CML patients who were treated with IM for at least 18 months and their treatment responses, were recorded. The mutation analysis was done using allele-specific oligonucleotide reverse transcriptase-polymerase chain reaction (RT-PCR) assay followed by direct sequencing technique. Forty-two patients (70%) were found to have IM-resistance. Five out of 42 patients had detectable T315I mutation. Median OS of IM-resistant T315I-mutated patients was 96 months (95% CI:54-138) compared to 84 months (95% CI:48-120) in non T315I-mutated patients, although this was found to be statistically insignificant (p = 0.43). The present study showed a higher prevalence of T315I mutation as compared to a few local studies. Median OS of T315I-mutated patients were observed to be longer than non-T315-mutated patients. Further studies encompassing larger cohort of patients are required to confirm this finding.